IS IT POSSIBLE TO OVERCOME THE CRISIS IN THE DEVELOPMENT OF THE HUMAN SYSTEM - Bondarenko Valentina (European Scientific Journal, ESJ, 2014)
The article states that developed a new methodology in the development of knowledge of the laws of the human system. This methodology made it possible to define that there have been and are only two paradigms of the human system development in the entire multicentury course of the human community development. Cycles, crises, chaos and all negative phenomena are nothing else but natural products of the second, indirect paradigm of development. The new model of living arrangement at each local level based on the direct relationship between production and consumption of a particular person, but a new high-tech level. Practical realization of this model is the only feasible precondition for the transition to sustainable and crisis-free development.